Analisis Pengaruh Modal, Kinerja SDM, Peran Pemerintah Dan Teknologi Terhadap Perkembangan Usaha Mikro, Kecil Dan Menengah Di Kecamatan Ungaran Barat - Mayandha Zulfa Poetri Utomo; Abdul Aziz (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
aim of this research is to find out the influence of capital, HR performance, the role of government and technology on the development of MSMEs in West Ungaran District. The population used in this research is traders who have MSME businesses whose business locations are in the West Ungaran District area who are domiciled in the Ungaran District area. The population was taken using data from BPS Semarang Regency in 2020, from this population a sample of 278 MSME traders in 2020 was obtained. West Ungaran District. This research method uses quantitative methods. The results of this research are that business capital, human resource performance, the role of government and technology have an important role in the development of MSMEs in West Ungaran District.